PERAN DIGITALISASI DALAM MENDUKUNG REFORMASI BIROKRASI: STUDI KASUS PADA INSTANSI PEMERINTAH KOTA TERNATE - Amalia, Rasti; Karianga, Hendra (Universitas Khairun, 2025)
Bureaucratic reform is an urgent need to improve the quality of state civil servants and realize good governance in Indonesia. Bureaucracy is often considered complicated, slow and unprofessional. To overcome this problem, the bureaucracy has intensified the principle of